Evaluation of Rosuvastatin Effect as Adjuvant Therapy to Methotrexate on Lipid Profile and the Possibility of its Cardioprotective Effect in Iraqi Patients with Active Rheumatoid Arthritis - Ehab M. Mikhael; Ibrahim A. Majeed; Faiq I. Gorial; Mohammad H. Al-Ossamy; Ali H. Falih; Dhikra Abdulhameed (Iraqi Journal of Pharmaceutical Sciences, 2017)
Rheumatoid arthritis (RA) is a common inflammatory disease that associated with increased morbidity and mortality due to accelerated atherosclerosis. Rosuvastatin is a unique hydroxy methyl glutaryl Co A (HMGCoA) reductase inhibitor that has anti inflammatory effects.